Conceptual Dimensions of Formative Assessment as Perceived by Curriculum Designers - Nematollahi, Parastoo; Daneshfar, Amirhosein (Assessment and Practice in Educational Sciences, 2023)
This study aimed to explore the conceptual dimensions of formative assessment as perceived by curriculum designers, focusing on their interpretations, challenges, and strategies within the context of curriculum development. A qualitative research design was employed using semi-structured interviews with 16 curriculum designers based in Tehran. Participants were selected through purposive sampling based on their expertise in curriculum planning and assessment. Interviews continued until theoretical saturation was reached, ensuring depth and variation in the data. Transcripts of the interviews were analyzed thematically using NVivo software, with open coding leading to the development of subthemes and overarching categories. Three main thematic categories emerged from the data: (1) pedagogical foundations of formative assessment, (2) implementation challenges and contextual barriers, and (3) strategic approaches to effective practice. Participants emphasized the role of formative assessment in supporting learning processes, fostering learner autonomy, and aligning with constructivist principles. However, systemic obstacles such as institutional constraints, teacher readiness, and policy misalignment were identified as major barriers. Strategic solutions proposed by curriculum designers included enhanced professional development, collaborative curriculum design, and the integration of technology. The findings underscored the need for a cultural and structural shift to effectively embed formative assessment into curriculum frameworks. Curriculum designers hold nuanced and pedagogically grounded conceptions of formative assessment, viewing it as a dynamic and learner-centered process. However, translating these conceptions into practice remains challenging due to systemic and contextual limitations. Addressing these challenges requires multi-level interventions including policy reform, professional development, and curriculum innovation aimed at creating a sustainable culture of formative assessment.